The Influence of Sagittal Proximal Tibial Anatomy in Tibial Intramedullary Nailing. Issue 11 (November 2020) - Cinats, David J.; Viskontas, Darius; Boyer, Dory; Perey, Bertrand; Stone, Trevor
Abstract : Objectives: To quantify anatomic variation in sagittal proximal tibial anatomy and determine if anatomy or nail insertion method influences the radiographic nail position. Design: Retrospective cohort of prospectively collected data. Setting: Level 1 trauma center. Patients/Participants: Forty-five patients with 46 tibia fractures (OTA/AO 41A, 42, and 43) treated with infrapatellar (IP) or suprapatellar (SP) nailing. The average patient age was 40.6 years (range 19–62 years). Intervention: Patients received IP or SP nailing. Cohorts were analyzed based on the nailing technique and proximal tibial anatomy. Main Outcome Measurements: Proximal tibial radiographic anatomy was quantified using novel measurements [anterior tubercle angle (ATA) and entry point position (EPP)]. Nail entry point, entry point displacement after reaming, nail position, and quality of reduction was measured and compared between groups. Results: ATA was highly variable between patients. ATA was strongly correlated with EPP with a higher ATA associated with EPP more colinear with the intramedullary canal. Patients with low ATA treated with IP nailing had significantly longer operative times (60.0 vs. 45.7 minutes). Low ATA tibias had a higher incidence of entry point displacement due to eccentric reaming compared with high ATA tibias (70% vs. 38%) with the highest incidence of entry point displacement and absolute displacement in low ATA tibias treated with IP nailing (86%, 2.8 mm). SP nailing demonstrated shorter operative times relative to IP nailing (45.5 vs. 55.6 minutes). Conclusions: There is considerable variability in proximal tibial anatomy and these features influences the nail position within the tibia. These differences in anatomy should be considered to potentially reduce operative times, entry point displacement and anteriorization of tibial nails. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.